Carbon Policy Effectiveness in Indonesia's Electricity Generation Subsector - Tasya Dwi Farlian Putri; Arie Dipareza Syafei (International Journal of Science and Environment (IJSE), 2026)
Climate change has increased the urgency of strengthening greenhouse gas (GHG) mitigation policies in energy systems. In Indonesia, the electricity generation subsector is strategically important because it remains closely linked to fossil fuel use while also becoming a central arena of national energy transition policy. This study aims to develop a system dynamics model for simulating the effect of carbon policy on GHG emissions in Indonesia's electricity generation subsector, evaluating the effectiveness of existing carbon policy pathways, and formulating policy directions based on scenario results and policy lessons from selected countries. The study applies a quantitative system dynamics approach using Causal Loop Diagram and Stock and Flow Diagram modelling in Vensim. The model represents interactions among demographic drivers, electricity demand, fossil and renewable generation capacity, fossil fuel consumption, carbon policy variables, and GHG emissions. Three scenarios were simulated: a baseline scenario, a 2030 medium-term target scenario, and a 2060 Net Zero Emission scenario. Model validation using MAPE indicated acceptable historical fit for population and power-generation emission variables. The results show that the baseline follows a high-emission pathway under weak policy pressure. The 2030 scenario reduces emissions to 196.42 MtCO2, below the 250 MtCO2 target. However, the 2060 scenario still leaves 127 MtCO2e of residual emissions, indicating that the Net Zero target is not fully achieved. The findings suggest that carbon policy is effective in the medium term but requires stronger integration with coal phase-down, renewable expansion, MRV, enforcement, and transition finance for long-term mitigation.